A ditadura no gatilho: reflexões sobre a violência policial militar - Burato, Jose Antonio [UNIFESP] (2015)
Based on the Louis Althusser theory of ideology and the principles of institutionalization of behaviors, this task aims to reflect about the causes of the violence from the military police in Brazil and the consequences to society, aiming to formulate possible proposals for the containment or reduction of this violence, adapting the national public security system to the democratic rule of Brazilian law. Therefore, we will study the military dictatorship in Brazil (1964-1985), since we believe to be the historical origin of this current characteristic of the brazilian police violence; We discuss the formation of the Military Police of São Paulo which for us will be reference to the other brazilian military police (other states); and we will check the context in which it occurred the process of democratic transition in the country, to understand the reasons of constitutional maintenance of this undemocratic framework that is the public security system in Brazil.